Inequality aversion and reciprocity in moonlighting games - Dirk Engelmann; Martin Strobel (Games, 2010)
We study behavior in a moonlighting game with unequal initial endowments. In this game, predictions for second-mover behavior based on inequality aversion are in contrast to reciprocity. We find that inequality aversion explains only few observations. The comparison to a treatment with equal endowments supports the conclusion that behavior is better captured by intuitive notions of reciprocity than by inequality aversion. Extending the model by allowing for alternative reference points promises better performance, but leads to other problems. We conclude that the fact that inequality aversion often works as a good short-hand for reciprocity is driven by biased design choices.
Keywords: 330; reciprocity; inequality aversion; altruism; moonlighting game